Novel Broccoli Sulforaphane-Based Analogues Inhibit the Progression of Pancreatic Cancer without Side Effects - Christina Georgikou; Laura Buglioni; Maximilian Bremerich; Nico Roubicek; Libo Yin; Wolfgang Gross; Carsten Sticht; Carsten Bolm; Ingrid Herr (Biomolecules, 2020)
The naturally occurring isothiocyanate sulforaphane, found in Brassicaceae vegetables, is promising in cancer treatment, e.g., by the normalization of enhanced levels of NF-κB-signaling in tumor stem cells. We chemically synthesized seven sulforaphane analogues by substitution of the sulfinyl group (S(O)) to either sulfimidoyl (S(NR)) or sulfonimidoyl (S (O) (NR)) groups, and characterized them in the cell lines of pancreatic cancer and several other tumor entities, including the NCI-60 cell panel. MTT and colony forming assays, flow cytometry, immunohistochemistry, microRNA arrays, bioinformatics, tumor xenotransplantation, and Kaplan Meier survival curves were performed. Compared to sulforaphane, the analogue SF102 was most efficient in inhibition of viability, colony formation, tumor growth, and the induction of apoptosis, followed by SF134. Side effects were not observed, as concluded from the body weight and liver histology of chick embryos and survival of C. elegans nematodes. Among 6659 differentially regulated microRNAs, miR29b-1-5p, and miR-27b-5p were downregulated by sulforaphane compared to controls, but upregulated by SF102 and SF134 compared to sulforaphane, suggesting differential signaling. Each substance was involved in the regulation of several NF-κB-related target genes. In conclusion, sulforaphane analogues are promising for the development of highly active new drugs in cancer treatment.